2000
DOI: 10.1046/j.1432-1327.2000.01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin stimulates NHE1 activity by sequential activation of phosphatidylinositol 3‐kinase and protein kinase C ζ in human erythrocytes

Abstract: The signaling cascade linking insulin receptor stimulation to the activation of Na/H exchanger (NHE) was investigated in human erythrocytes, a simple cell model expressing the NHE1 isoform and protein kinase C (PKC) a and z isoforms only. Our results demonstrate the presence of phosphatidylinositol (PtdIns) 3-kinase in these cells and its activation by insulin. With a similar time-course, insulin also promoted both the translocation and activation of PKC z, but had no effect on PKC a. Inhibition of PtdIns 3-ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
64
1
2

Year Published

2001
2001
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 46 publications
4
64
1
2
Order By: Relevance
“…52,53 Along these lines, the observation that established PI 3-K inhibitors such as wortmannin and LY294002 are able to inhibit PDGF-induced NHE1 activity confirms that PI 3-K is also involved in the regulation of NHE1 in human HSC after stimulation with PDGF. In keeping with this observation, the effect of canrenone on NHE1 activity could be ascribed to its inhibitory effect on PI 3-K activity.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…52,53 Along these lines, the observation that established PI 3-K inhibitors such as wortmannin and LY294002 are able to inhibit PDGF-induced NHE1 activity confirms that PI 3-K is also involved in the regulation of NHE1 in human HSC after stimulation with PDGF. In keeping with this observation, the effect of canrenone on NHE1 activity could be ascribed to its inhibitory effect on PI 3-K activity.…”
Section: Discussionmentioning
confidence: 91%
“…Studies performed on different cell types have shown that activation of the NHE1 after stimulation with PDGF is dependent on the activation of different intracellular signaling pathways, including the Ras-mediated ERK cascade 48,50 and Ras-independent signaling cassettes such as the Nck-interacting kinase 51 and PI 3-K. 35 Particularly concerning PI 3-K involvement, activation of NHE1 by PDGF is blocked by preincubation with PI 3-K inhibitors, such as wortmannin, or by inhibition or down-regulation of protein kinase C. 35,52 More precisely, the isozyme of protein kinase C has been shown to be a downstream target of phosphatidylinositol 3,4,5-phosphate and to mediate the PI 3-K activation of NHE1. 52,53 Along these lines, the observation that established PI 3-K inhibitors such as wortmannin and LY294002 are able to inhibit PDGF-induced NHE1 activity confirms that PI 3-K is also involved in the regulation of NHE1 in human HSC after stimulation with PDGF.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of isoproterenol on insulin-stimulated glucose transport were mimicked by acidification and reversed by alkalinisation of the adipocytes, suggesting the effects of insulin are pH sensitive [24]. Insulin has been proposed to stimulate alkalinisation by stimulation of Na + /H + exchange in erythrocytes and myocytes [24,25]. However, Na + /H + exchange has been shown to be elevated in vascular smooth muscle cells derived from SHRSP [26], arguing against a role for reduced cell alkalinisation in aberrant insulin-stimulated GLUT4 translocation in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…These include pertussis toxin-sensitive G protein ␣ subunits (45), G protein ␤␥ subunits (32), PKC (12)(13)(14), the Ras-mitogen-activated protein kinase/ extracellular signal-regulated kinase kinase-extracellular signal-regulated kinase kinase pathway (7)(8)(9)(10), and Src family kinases (25). Although it has been shown that members of the Src family are volume-sensitive enzymes (11,16,17), our results do not support their role in the osmotic activation of NHE-1, which is in agreement with the study by Kapus et al (17).…”
Section: Discussionmentioning
confidence: 99%
“…These include mitogen-activated protein kinases such as extracellular signal-regulated protein kinase (ERK), stress-activated protein kinases (c-Jun N-terminal kinases) (7)(8)(9)(10), Src family tyrosine kinases p59 fgr and p56/59 hck (11), protein kinase C (12)(13)(14), Janus kinase (15), and phosphatidylinositol 3-kinase (13), although there is not a consensus that any of those kinases mediate hypertonicity-induced activation of NHE-1.…”
mentioning
confidence: 99%